Applications of Digital Image Processing XXVI 2003
DOI: 10.1117/12.510037
|View full text |Cite
|
Sign up to set email alerts
|

Software tools for assisting the multisource imagery analyst

Abstract: Increasingly demanding military requirements and rapid technological advances are producing reconnaissance sensors with greater spatial, spectral and temporal resolution. This, with the benefits to be gained from deploying multiple sensors co-operatively, is resulting in a so-called data deluge, where recording systems, data-links, and exploitation systems struggle to cope with the required imagery throughput. This paper focuses on the exploitation stage and, in particular, the provision of cueing aids for Ima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 3 publications
0
2
0
Order By: Relevance
“…In general terms, it can be said that the data that predominate in the military context are more complex to process than those in a conventional organization. In the study we have carried out, the main sources found are biometric data, e.g., from electroencephalograms [70]; data from military experts and commanders (e.g., field assessments and weaponry needed in that particular field), which should be used in conjunction with the other data to build decision systems [35]; the Internet of things, smart and connected devices widely used by the military, generating large volumes of information over time [71], e.g., those provided by radars [72]; the Internet of battlefield things, which connects soldiers with smart technology in weapons and other objects to give troops "extra sensory powers" [73]; military personnel data, e.g., those obtained in screening interviews [74]; military veterans' data obtained, e.g., from their administrative personal files [75]; and other data, both internal and open in any format (including videos, images and speeches), e.g., those coming from unmanned aerial vehicles [76], videos for facial recognition [77,78], data from the Internet, etc. ; -Insight generation for military.…”
Section: Discussionmentioning
confidence: 99%
“…In general terms, it can be said that the data that predominate in the military context are more complex to process than those in a conventional organization. In the study we have carried out, the main sources found are biometric data, e.g., from electroencephalograms [70]; data from military experts and commanders (e.g., field assessments and weaponry needed in that particular field), which should be used in conjunction with the other data to build decision systems [35]; the Internet of things, smart and connected devices widely used by the military, generating large volumes of information over time [71], e.g., those provided by radars [72]; the Internet of battlefield things, which connects soldiers with smart technology in weapons and other objects to give troops "extra sensory powers" [73]; military personnel data, e.g., those obtained in screening interviews [74]; military veterans' data obtained, e.g., from their administrative personal files [75]; and other data, both internal and open in any format (including videos, images and speeches), e.g., those coming from unmanned aerial vehicles [76], videos for facial recognition [77,78], data from the Internet, etc. ; -Insight generation for military.…”
Section: Discussionmentioning
confidence: 99%
“…At Dstl a testbed system (Privett et al, 2003) has been developed to provide computer aided assistance to IAs, aimed in particular at automating some routine aspects of their workload and at directing the analyst's attention towards features of potential interest. The IA can then focus on problems that require their experience and reasoning skills rather than on mundane -but, nonetheless, essential -image handling tasks.…”
Section: Introductionmentioning
confidence: 99%